Histochemical Analysis and Distribution of Digestive Enzymes in the Gastrointestinal System of the European Barracuda Sphyraena sphyraena (Linnaeus, 1758) - Ivana Tlak Gajger; Srebrenka Nejedli; Zvonimir Kozarić; Josipa Vlainić (Animals, 2024)
In this study, we examined the gastrointestinal tract of the European barracuda (Sphyraena sphyraena) living in the Adriatic Sea near Dubrovnik, Croatia. The study aimed to identify the presence and distribution of four digestive enzymes: alkaline phosphatase, aminopeptidase, acid phosphatase, and non-specific esterase. We found that alkaline phosphatase activity was present in the brush border of the enterocytes in all the investigated intestinal segments. The activity of the alkaline phosphatase was the strongest in the pyloric caeca but strong only in the basal part of the intestinal villi in the anterior and middle intestinal segments. In the posterior intestinal segment, alkaline phosphatase had strong activity along the entire villi. The activity of acid phosphatase was weak in all the investigated parts of the intestine, except in the posterior part, where it was moderate. Aminopeptidase was detected in the brush border of the intestinal epithelium, with stronger activity in the pyloric caeca and anterior part of the intestine and weaker activity posteriorly. The activity of the non-specific esterase was moderate in the pyloric caeca and anterior part of the intestine, while it was weak in the posterior segment and the lamina propria in all parts of the digestive tract. Weak acid phosphatase activity was observed only in the lamina propria of the posterior part of the intestine. This study is the first to evaluate the activity of digestive enzymes in the European barracuda.